2019
DOI: 10.1002/ajcp.12332
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Familial Incarceration and Ethnic Identity in Suicidal Ideation and Suicide Attempt: Findings from a Longitudinal Study of Latinx Young Adults in California

Abstract: Highlights• Incarceration has not been studied in the context of ethnic minority adult suicide behavior.• High affective ethnic identity scores were inversely associated with lifetime suicide attempt.• Ethnic identity moderated the association between parental incarceration and suicidal ideation.Abstract Suicide is a leading cause of death among young adults; however, contextual risks and cultural factors are rarely studied in the context of ethnic minority suicidal ideation (SI) and suicidal attempt (SA). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 91 publications
1
13
0
Order By: Relevance
“…This finding aligns with research demonstrating that social support can limit the physiological arousal and stress reactivity associated with traumatic circumstances and promote resilient functioning [ 121 , 122 ]. Despite the protective effects of strong bonds with teachers, peers, and members of important community groups for ACE-exposed populations [ 85 , 123 , 124 ], support from peers may be insufficient or need to be paired with direct services or additional individual or social assets to mitigate the negative effects of high levels (≥4 HHD) of adversity for PSU and PIU.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with research demonstrating that social support can limit the physiological arousal and stress reactivity associated with traumatic circumstances and promote resilient functioning [ 121 , 122 ]. Despite the protective effects of strong bonds with teachers, peers, and members of important community groups for ACE-exposed populations [ 85 , 123 , 124 ], support from peers may be insufficient or need to be paired with direct services or additional individual or social assets to mitigate the negative effects of high levels (≥4 HHD) of adversity for PSU and PIU.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be mediated by factors associated with social exclusion, including a lack of belonging as result of factors such as ethnicity. This suggests a need for children and young people with an incarcerated family member to be better supported in the community to build their resilience (Forster et al, ). Young people who are exposed to a family member who is experiencing suicidal ideation are also at increased risk, so family support is essential during the early years of a child's development (Goodday, Shuldiner, Bondy, & Rhodes, ).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Studies not specific to Hispanic teens, i.e., across all ethnicities, indicated that the support of parents and friends was protective against suicidal ideation and suicidal behaviors [ 6 ]. For Hispanics of both sexes, a strong sense of ethnic identity was protective against suicidal ideation and suicide attempt, and a strong ethnic identity moderated the increased risk of suicidal behaviors associated with having an incarcerated family member [ 28 ]. Strong cultural connections, which seem to correlate with strong mother–daughter relationships, was associated with a reduced risk of suicide attempts for female Hispanics [ 29 ].…”
Section: Introductionmentioning
confidence: 99%